2015
DOI: 10.1177/1687814015582120
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of non-linear bearings using the Hilbert–Huang transform

Abstract: Changes in the performance of bearings can significantly vary the distribution of internal forces and moments in a structure as a result of environmental or operational loads. The response of a bearing has been traditionally idealized using a linear model but a non-linear representation produces a more accurate picture at the expense of modelling complexity and computational time. In this article, a lead rubber bearing is idealized using the hysteretic Bouc-Wen model. The Hilbert-Huang transform is then employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The boundary conditions of the bridge are modeled using rotational springs at the left ( K 1 ) and right ( K 2 ) supports. Other researchers use the hysteretic Bouc–Wen model to represent the translational stiffness of the bearing and to predict the response of an existing bridge (Gutierrez Soto & Adeli, 2019) or the parameters of the bearing model in real time from the forces directly applied to the bearing using the Hilbert–Huang transform (González & Aied, 2015) or a Bayesian framework (Yuen et al., 2019). This paper assumes that a linear approximation of the rotational response will suffice to assess a change in support conditions in the presence of small traffic loads.…”
Section: Estimation Of the Contact Point Responsementioning
confidence: 99%
“…The boundary conditions of the bridge are modeled using rotational springs at the left ( K 1 ) and right ( K 2 ) supports. Other researchers use the hysteretic Bouc–Wen model to represent the translational stiffness of the bearing and to predict the response of an existing bridge (Gutierrez Soto & Adeli, 2019) or the parameters of the bearing model in real time from the forces directly applied to the bearing using the Hilbert–Huang transform (González & Aied, 2015) or a Bayesian framework (Yuen et al., 2019). This paper assumes that a linear approximation of the rotational response will suffice to assess a change in support conditions in the presence of small traffic loads.…”
Section: Estimation Of the Contact Point Responsementioning
confidence: 99%
“…In most bridge modelling applications, linear models are employed to capture the structural behaviour of the bridge. In these models, the bridge supports are idealized and assumed to behave as perfect roller or pin supports while, in reality, bearing friction often causes the supports to behave in a non-linear fashion (Ülker Kaustell 2017; González and Aied 2015). At low excitation amplitudes, bearings designed as roller supports can act as fixed bearings (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that, because of the inappropriate function of the expansion joints (due to accumulation of debris and the temperature differential), the boundary conditions of the structure were altered, causing alteration in the resonant frequencies of the bridge. González and Aied[52] employed the Hilbert-Huang transform to characterize the features and identify the changes in the response of a lead rubber bearing. However, the accuracy of the proposed method was limited by the noise level.…”
mentioning
confidence: 99%